2013
DOI: 10.1016/s0924-9338(13)75721-3
|View full text |Cite
|
Sign up to set email alerts
|

308 – Apocalyptic delusions

Abstract: This study attempts to present the genesis of the world end (Apocalyptic) delusions. Religious idea of the world end given in the Sacred Scripture is being found in the content of delusions but is added with inclusion of modern cultural signs, personal values and beliefs and description of apocalypse, produced in delusional thinking of nowadays patients suffering from schizophrenia and related disorders.We have studied the content of delusions in patients with schizophrenia looking for apocalyptic themes using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Rudalevicienel and colleagues [68] have indicated that religious based delusions may take on a cultural pattern within different groups. In their study of apocalyptic delusions, they found these types of delusions to be cross-cultural regardless of religious background.…”
Section: Religious Delusions and Schizophreniamentioning
confidence: 99%
“…Rudalevicienel and colleagues [68] have indicated that religious based delusions may take on a cultural pattern within different groups. In their study of apocalyptic delusions, they found these types of delusions to be cross-cultural regardless of religious background.…”
Section: Religious Delusions and Schizophreniamentioning
confidence: 99%